A simple management of massive bone defect after en-bloc resection of osteofibrous dysplasia of tibial shaft: A case report. (August 2021) - Kamal, Achmad Fauzi; Ramang, Didi Saputra
Abstract: Introduction: Osteofibrous dysplasia is a relatively rare disease, exclusively found in children, affecting the tibial diaphysis. Various management approaches are already available, but an internationally approved management guideline is not yet established. There is a major concern in the current management of wide excision technique as it frequently results in massive bone defect. Case presentation: Here we present a case of osteofibrous dysplasia on a 10-year-old girl in Cipto Mangunkusumo Hospital with chief complaint of mild persistent pain of her lower leg since two years before with slight bowing deformity. The radiograph and histopathological examination support the diagnosis of osteofibrous dysplasia. She was managed with en-bloc resection (wide excision) of the tumor, followed with reconstruction using biomaterials substitute; combination between demineralized bone matrix (Bonegener R ) and bone substitute "hydroxyapatite and calcium sulphate" and internal fixation using plate and screw. Results: Clinical and radiological evaluation showed successful improvement and outcome. The patient showed progressive functional outcomes and achieved functional score of 100% LEFS at 3 years follow-up. The plate and screw was removed at 48 weeks after adequate callus formation andradiological union was achieved. Conclusion: Simple reconstruction using biomaterial bone substitute not only created new bone formation with good stability, but also enabled patient to have an improved quality of life. This method is recommended to overcome the massive bone defect after tumor resection in osteofibrous dysplasia patient. Highlights: An international agreement of management pathway is not yet established It is commonly wide excision that keep leaving massive bone defect Several surgery approaches sometimes cause complication Simple reconstruction using biomaterial bone substitude achieved good radiological outcome and good the patient's quality of life